Family subsidy; a positive impact for the society (2015)
family subsidy in the world with different names, features and levels of protection. But their goal is the same: to establish affiliates aid the labor system in accordance with their family obligations, including food appear both economic benefits, social programs dependent children, parents and others. In the world, social security systems have valued family obligations, even though they are not necessarily considered a contingency or require exceptional protection in all matters relating to the care of the family, since it is a social necessity which entails significant costs for citizens.